Efeito da inércia térmica em edifícios de escritórios: estudo de caso em Belo Horizonte, MG - Jussara Grosch Ludgero Ramos (2010)
In regard of the importance of the thermal performance in the energy consumption on commercial buildings, this dissertation presents a study about one o the most important consumer groups in Brazil, the office building. It is known that in this kind of building the thermo-physical properties of envelope materials and components have the great influence in the building thermal performance, being responsible for the high consume by the use of artificial air condition. Therefore, this dissertation presents an analysis of the influence of the thermal inertia of a typical office building by a case study in Belo Horizonte, MG. The methodology used was the experimental analysis by means of a parametric computational simulation in the EnergyPlusR program and empirically validated. The validation was made by the measurement of climatic variables and internal environmental variables monitoring. The parametrics experiments are based on the changing of the architectonical and constructive characteristics of the facade. The prototypes vary in function of the following parameters: classes of inertia of the external walls, glazed area of the facade, inclusion of solar protection of the translucent areas. It was observed that the thermal inertia is function of the building facade typology and varies in accordance with the percentage of the glazed area of the facade, the solar protection of the facade translucent areas, air infiltration, and, at lesser extent, the thermal mass of the external walls. It was concluded that, for the office building typology, the constructive material of the walls do not have expressive influence on the internal air temperature. The results obtained contribute to a theoretical understanding of the thermal inertia phenomena, as well as the thermal performance valuation of the office buildings situated in tropical climate of altitude.